Biological responses of the predatory blue crab and its hard clam prey to ocean acidification and low salinity - Longmire, Katherine S.; Seitz, Rochelle D.; Seebo, Michael S.; Brill, Richard; Lipcius, Rom (W&M ScholarWorks, 2022)
How ocean acidification (OA) interacts with other stressors is understudied, particularly for predators and prey. We assessed long-term exposure to decreased pH and low salinity on (1) juvenile blue crab Callinectes sapidus claw pinch force, (2) juvenile hard clam Mercenaria mercenaria survival, growth, and shell structure, and (3) blue crab and hard clam interactions in filmed mesocosm trials. In 2018 and 2019, we held crabs and clams from the Chesapeake Bay, USA, in crossed pH (low: 7.0, high: 8.0) and salinity (low: 15, high: 30) treatments for 11 and 10 wk, respectively. Afterwards, we assessed crab claw pinch force and clam survival, growth, shell structure, and ridge rugosity. Claw pinch force increased with size in both years but weakened in low pH. Clam growth was negative, indicative of shell dissolution, in low pH in both years compared to the control. Growth was also negative in the 2019 high-pH/low-salinity treatment. Clam survival in both years was lowest in the low-pH/low-salinity treatment and highest in the high-pH/high-salinity treatment. Shell damage and ridge rugosity (indicative of deterioration) were intensified under low pH and negatively correlated with clam survival. Overall, clams were more severely affected by both stressors than crabs. In the filmed predator-prey interactions, pH did not substantially alter crab behavior, but crabs spent more time eating and burying in high-salinity treatments and more time moving in low-salinity treatments. Given the complex effects of pH and salinity on blue crabs and hard clams, projections about climate change on predator-prey interactions will be difficult and must consider multiple stressors.